Sex differences in faecal occult blood test screening for colorectal cancer - Koskenvuo, L. (Br J Surg, 2018)
BACKGROUND: This analysis of patients in a randomized population‐based health services study was done to determine the effects of faecal occult blood test (FOBT) screening of colorectal cancer (CRC) in outcomes beyond mortality, and to obtain explanations for potential sex differences in screening effectiveness. METHODS: In the Finnish FOBT screening programme (2004–2011), people aged 60–69 years were randomized into the screening and control arms. Differences in incidence, symptoms, tumour location, TNM categories, non‐vital outcomes and survival in the screening and control arms were analysed. RESULTS: From 321 311 individuals randomized, 743 patients with screening‐detected tumours and 617 control patients with CRC were analysed. CRC was less common in women than in men (0·34 versus 0·50 per cent; risk ratio (RR) 0·82, 95 per cent c.i. 0·74 to 0·91) and women were less often asymptomatic (16·7 versus 22·0 per cent; RR 0·76, 0·61 to 0·93). Women more often had right‐sided tumours (32·0 versus 21·3 per cent; RR 1·51, 1·26 to 1·80). Among men with left‐sided tumours, those in the screening arm had lower N (RR 1·23, 1·02 to 1·48) and M (RR 1·57, 1·14 to 2·17) categories, as well as a higher overall survival rate than those in the control arm. Furthermore among men with left‐sided tumours, non‐radical resections (26·2 versus 15·7 per cent; RR 1·67, 1·22 to 2·30) and postoperative chemotherapy sessions (61·6 versus 48·2 per cent; RR 1·28, 1·10 to 1·48) were more frequent in the control arm. Similar benefits of screening were not detected in men with right‐sided tumours or in women. CONCLUSION: Biennial FOBT screening seems to be effective in terms of improving several different outcomes in men, but not in women. Differences in incidence, symptoms and tumour location may explain the differences in screening efficacy between sexes.